(untitled) (European Journal of Interdisciplinary Research and Development, 2023)
Communication is the main form of interpersonal relations, with the help of which people communicate with each other mentally, exchange information, influence each other, feel each other and understand. Therefore, communication as a socio-psychological phenomenon takes part in all spheres of social life and arises as a need for material, spiritual, cultural, emotional, motivational aspects of cooperation. Satisfying all kinds of human needs in accordance with the purpose depends on the ritual of communication, and interpersonal relations serve to resolve ideals of a perfect generation and a perfect person.